Indonesia’s Breakthrough in Maximizing Wind Energy Efficiency Through Optimized Blade Configuration: Terobosan Indonesia dalam Memaksimalkan Efisiensi Energi Angin Melalui Konfigurasi Blade yang Dioptimalkan - Prasetiyo , Rohmad Arvendo Yoga; Firdaus, Eng Rahmad (Indonesian Journal of Innovation Studies, 2024)
Indonesia faces rising energy demand, risking an energy crisis and increased fossil fuel dependence. This study explores using NACA 0021 airfoil blades to improve wind turbine performance by analyzing the effect of different rotor blade numbers. Conducted at Universitas Muhammadiyah Sidoarjo, the research tested turbines with 2, 3, and 4 blades, measuring current, voltage, power, and efficiency. Results showed that more rotor blades enhance turbine performance, increasing current and voltage output. This suggests optimizing blade configurations can significantly boost small-scale wind energy systems, helping reduce fossil fuel reliance and mitigate the energy crisis. Highlights: 1. More rotor blades boost turbine performance: increased current and voltage. 2. NACA 0021 airfoil optimizes small-scale power generation. 3. Effective blade configuration reduces fossil fuel reliance, mitigating energy crises. Keywords: wind energy, NACA 0021, rotor blades, turbine performance, renewable energy